Quality Benchmarking for Online Writing Course: A Malaysian Case Study - Mat Daud, Nuraihan; Farrah, Mohammed Hakim (IDOSI Publication, 2013)
The demand for online programmes is increasing and more institutions are opting to offer online courses. To make confident judgments concerning the efficiency of this mode of delivery, it is necessary to carry out an evaluation. This paper discusses an evaluation conducted on an online English for Academic Writing course offered by a public university in Malaysia and the reaction of the institution to the findings. The adapted version of the Institute of Higher Education Policy (IHEP 2000) benchmarks was used to determine if the course met the quality benchmarks for online learning. This was complemented by interviews with the teachers. Results show that support was lacking and management of the online mode needed to be improved. Steps were then taken to improve the programme by addressing the weaknesses identified in the study. The study also shows that it is not possible to evaluate the results of the implementation within a short period of time. The process of change takes time especially where the adoption of technology is concerned.